Analysis of Accountability and Supervision and Solutions to Guidance and Counseling Problems - Afifah; Neviyarni S; Yarmis Sukur (Journal Of Psychology, Counseling And Education, 2025)
Understand the concept of accountability and supervision in the context of guidance and counseling, as well as to identify the requirements, forms, criteria, supporting factors, obstacles, implications, problems and solutions related to the implementation of accountability and supervision.  The research methodology used is the library method, where information is collected from various literary sources such as books, scientific reports and journal articles. Literature research is used to collect relevant information from various sources to support analysis of the concepts of accountability and supervision. The research results show that the concept of accountability and supervision in the context of guidance and counseling includes an understanding of responsibility to be accountable for performance or actions to the authorities. Accountability involves responsibility for performance results and services provided, while supervision involves monitoring and evaluation to ensure that organizational operations follow established procedures and guidelines. The implementation of accountability and supervision involves supporting and inhibiting elements as well as suggested solutions.